Determinan Behavioral Intention Penggunaan Peer-to-peer lending Syariah Di Indonesia: Model UTAUT2 - Subambang Harsono; Yusri Yusri; Chairina Chairina (Jurnal Prodi Fakultas Ekonomi-UISU, 2023)
Financial technology developed a concept, peer-to-peer lending, that enables access to funding without the role of financial institutions such as banks. However, data shows that market share of Islamic peer-to-peer lending is still very small compared to the peer-to-peer lending industry as a whole. Therefore, further efforts are needed to increase the market share of Islamic peer-to-peer lending. This study attempts to understand factors influencing behavioral intention of users (as a funders) to use Islamic peerto-peer lending with the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) approach. Using the judgment sampling method, 157 Islamic peer-to-peer lending users were collected as respondents. This research was conducted using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method and use SmartPLS 3.0 software to test the proposed model. The results show that performance expectancy, price value, and habit have a positive influence on behavioral intention to use Islamic peer-to-peer lending, where performance expectancy has the biggest influence.